Crime Investigation in the Mahabharata Novel by Nyoman S. Pendit (Forensic Linguistic Study) - Fitrah, Yundi; Putra, Yoga Mestika; Putri, Aprilia Kartika; Fitriah, Siti (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
The criminal case in the novel